Successful Treatment of Spontaneous Cerebrospinal Fluid Rhinorrhea With Endoscopic Third Ventriculostomy and Lumboperitoneal Shunt: A Case Report - Tang, Chao; Zhu, Junhao; Feng, Kaiyang; Yang, Jin; Cong, Zixiang; Cai, Xiangming; Qiao, Liang; Ma, Chiyuan (Frontiers in Neuroscience, 2020)
Spontaneous cerebrospinal fluid (CSF) rhinorrhea represents an important clinical entity that is being observed with increasing prevalence, ranging from 14 to 55%. Spontaneous CSF rhinorrhea is associated with elevated intracranial pressure (ICP), which is rarely stopped without surgical intervention. Endoscopic endonasal repair is typically warranted for CSF rhinorrhea. However, the recurrence rate of CSF leaks after the endoscopic endonasal repair of skull base defects due to ICP is usually high. We describe a 25-year-old man without a history of head injury, tumor, or obesity. The onset of his symptoms occurred in 1 week in the form of a persistent clear left nostril rhinorrhea. Computed tomography (CT) and magnetic resonance images (MRI) showed signs of CSF in the left sphenoidal sinus, meningocele in the left frontal sinus, empty sella, hydrocephalus, and Chiari I malformation (CIM). Cine-MRI revealed the flow of CSF was obstructed at the aqueduct and the outlet of the fourth ventricle. Endoscopic third ventriculostomy (ETV) was performed for the patient with obstructive hydrocephalus. Post-operative CSF pressure measurement demonstrated elevated ICP. The patient still had case of CSF rhinorrhea, and subsequently underwent lumboperitoneal shunt (LPS) for treatment of ICP. The patient showed a prompt resolution of CSF leak. Ten months later, the patient showed a significant improvement in terms of his herniated tonsil and cessation of CSF rhinorrhea.